Application of Fourier transform infrared spectroscopy to determine the reaction rate equation for cross-linking Matrimid 5218 with ethylenediamine in methanol - Yager, Kimberly Marie (Kansas State University, 2018)
The cross-linking reaction of the polyimide Matrimid 5218 with ethylenediamine (EDA) in methanol was investigated using Fourier transform infrared (FTIR) spectroscopy. Peaks associated with breaking imide bonds and the formation of amide bonds were identified. Using an internal standard peak of 1014 cm⁻¹ allowed for quantitative analysis to be applied. The peak areas, calculated by slice area, were used for absorbance ratio analysis to follow the cross-linking reaction as a function of time. Lastly, the absorbance values for the decreasing peak 1718 cm⁻¹ were used to calculate the order of reaction for the reaction rate of the mechanism.
Keywords: Polyimides; Matrimid 5218; Crosslinking; Fourier transform infrared spectroscopy; Reaction rate equation